Sprouty4 at the crossroads of Trk neurotrophin receptor signaling suppression by glucocorticoids - Ferrero Restelli, Facundo; Federicci, Fernando; Ledda, Fernanda; Paratcha, Gustavo (Frontiers in Molecular Neuroscience, 2023)
Glucocorticoids (GCs) affect neuronal plasticity, development and function of the nervous system by inhibiting neurotrophin-induced Trk signaling. It has been established that pretreatment with dexamethasone (DEX) restricts Neurotrophin-induced neurite outgrowth by inhibiting Trk-dependent activation of Ras-Erk1/2 signaling pathways. However, the precise molecular mechanism through which DEX interferes with neurotrophin signaling and Trk-mediated neurite outgrowth has not been clearly defined yet. Here, we observed that in PC12 cells DEX treatment promotes the transcription of Sprouty4, a regulatory molecule that is part of a negative feedback module that specifically abrogates Ras to Erk1/2 signaling in response to NGF. In line with this, either knockdown of Sprouty4 or overexpression of a dominant negative form of Sprouty4 (Y53A), rescue the inhibition of NGF/TrkA-promoted neurite outgrowth and Erk1/2 phosphorylation induced by DEX. Likewise, treatment of hippocampal neurons with DEX induces the expression of Sprouty4 and its knockdown abrogates the inhibitory effect of DEX on primary neurite formation, dendrite branching and Erk1/2 activation induced by BDNF. Thus, these results suggest that the induction of Sprouty4 mRNA by DEX translates into a significant inhibition of Trk to Erk1/2 signaling pathway. Together, these findings bring new insights into the crosstalk between DEX and neurotrophin signaling and demonstrate that Sprouty4 mediates the inhibitory effects of DEX on neurotrophin function.